Optimizing Glioblastoma Temozolomide Chemotherapy Employing Lentiviral-based Anti-MGMT shRNA Technology - Viel, Thomas (Nature Publishing Group, 2013)
Despite treatments combining surgery, radiation-, and chemotherapy, patients affected by glioblastoma (GBM) have a limited prognosis. Addition of temozolomide (TMZ) to radiation therapy is the standard therapy in clinical application, but effectiveness of TMZ is limited by the tumor's overexpression of the DNA repair protein O6-methylguanine-DNA methyltransferase (MGMT). The goal of this study was to use the highly specific and efficient RNA interference (RNAi) pathway to modulate MGMT expression to increase TMZ efficiency in chemotherapy resistant GBM. Using lentiviral-based anti-MGMT small hairpin RNA (shRNA) technology we observed a specific inhibition of the MGMT expression in GBM cell lines as well as in subcutaneous tumors. Tumor growth inhibition was observed following TMZ treatment of xenografts with low MGMT expression in contrast to xenografts with high MGMT expression. Bioluminescence imaging (BLI) measurements indicated that luciferase and shRNA-expressing lentiviruses were able to efficiently transduce the GBM xenografts in vivo. Treatment combining injection of a lentivirus expressing an anti-MGMT shRNA and TMZ induced a reduction of the size of the tumors, in contrast with treatment combining the lentivirus expressing the control shRNA and TMZ. Our data suggest that anti-MGMT shRNA therapy could be used in combination with TMZ chemotherapy in order to improve the treatment of resistant GBM.